The improvement of anti-HER2 scFv soluble expression in Escherichia coli (Brazilian Journal of Pharmaceutical Sciences, 2020)
The relationship between the expression of HER2 and malignity of breast tumors has led to the generation of antibodies targeting HER2+ tumors. In addition, the expression of scFvs, as the smallest antigen-binding region of antibody containing two disulfide bonds in Escherichia coli often results in accumulating non-functional protein in the cytoplasm. A redox-modified strain of E. coli such as Origami (DE3) may facilitate the formation of proper disulfide bond in cytoplasm. The present study aimed to optimize the expression of anti-HER2 scFv in Origami and evaluate the influence of induction temperature, and host strain on the solubility of the protein. To this aim, chemically synthesized anti-HER2 scFv of Trastuzumab was cloned in pET-22b (+). The results demonstrated that anti-HER2 scFv is expressed in Origami, purified by using Ni-NTA column, and detected by anti-His antibody in Western blot analysis. The highest anti-HER2 scFv expression in Origami was achieved 24 h after IPTG induction (1 mM) at 37 °C. Further, the total anti-HER2 scFv expression level was higher in BL21, compared to Origami strain. However, the ratio of soluble/insoluble forms of anti-HER2 scFv increased in Origami strain. Furthermore, higher soluble expression was achieved when the culture of recombinant Origami was conducted at lower temperature (25 °C).